Intraseasonal Variability of Air Temperature Over East Asia in Boreal Summer - Zhao, Chen; Li, Tim; Yao, Suxiang; Behera, Swadhin K.; Nasuno, Tomoe (Frontiers in Earth Science, 2017)
The intraseasonal oscillation (ISO) of atmospheric temperature at 2m over East Asia (EA) in boreal summer is investigated through NCEP-NCAR reanalysis data for the period of 1979-2013. It is found that the surface air temperature in EA has a dominant period of 10-30 days and exhibits a southeastward propagation characteristic. The average zonal and meridional phase speed of the intraseasonal air temperature anomaly is about 2.6 longitudes and 1.7 latitudes per day, respectively. A diagnosis of the temperature budget suggests that the propagation of the intraseasonal temperature perturbation is primarily attributed to the advection by the mean wind and the advection of the summer mean temperature by the intraseasonal wind. An upper-tropospheric geopotential positive (negative) height anomaly is closely associated with a low-level warmer (cooler) air temperature anomaly and both anomalies propagate southeastward in a similar way. A wave activity flux analysis reveals that mid-latitude Rossby wave energy also propagates southeastward, consistent with the upper-tropospheric geopotential height propagation. This indicates that in addition to low-level advection mechanism, upper-tropospheric forcing through the hydrostatic relationship is another possible mechanism. A further statistical analysis indicates that heat waves in EA summer are modulated by the southeastward-propagating intraseasonal temperature mode.